2023
DOI: 10.1038/s41598-023-42988-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of climate warming and human activities on the distribution patterns of Fritillaria unibracteata in eastern Qinghai-Tibetan Plateau

Dan Zhao,
Jun Wang,
Wei Dai
et al.

Abstract: Fritillaria unibracteata is an endangered medicinal material species endemic to the Qinghai Tibet Plateau, and belongs to the national Class III endangered plant. In addition to expelling wind and removing damne, it also warms menstruation and relieves pain in clinic use of tranditional Chinese medicine. In recent years, affected by the destruction of shrubs and climate change, the habitat of F. unibracteata wild resources has been seriously damaged, indicating of great significance to predict its potential su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
1
0
0
Order By: Relevance
“…As TSN and ART increase, there is a gradual shift from highly suitable areas to marginally suitable areas and eventually to unsuitable areas (Figure S1). The observed temperature sensitivity aligns with that of other endangered species on the Tibetan plateau, such as Fritillaria unibracteata, Paeonia decomposita, and Paeonia rotundiloba [17,44]. Furthermore, our study revealed that the distribution of C. gigantea is significantly affected by temperature and by precipitation patterns, particularly the PDQ.…”
Section: Discussionsupporting
confidence: 83%
“…As TSN and ART increase, there is a gradual shift from highly suitable areas to marginally suitable areas and eventually to unsuitable areas (Figure S1). The observed temperature sensitivity aligns with that of other endangered species on the Tibetan plateau, such as Fritillaria unibracteata, Paeonia decomposita, and Paeonia rotundiloba [17,44]. Furthermore, our study revealed that the distribution of C. gigantea is significantly affected by temperature and by precipitation patterns, particularly the PDQ.…”
Section: Discussionsupporting
confidence: 83%